2009
DOI: 10.1002/pssc.200880838
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thermal anneal steps on the current collapse of fluorine treated enhancement mode SiN/AlGaN/GaN HEMTs

Abstract: Gallium nitride based high electron mobility transistors offer high carrier density combined with high electron mobility and enable operation at high frequencies, voltages and temperatures. However, they are generally working in depletion mode, requiring a negative bias to switch them off. As this is disadvantageous for circuit design, power consumption and safety of operation, enhancement mode devices would be favourable. This operation mode can be reached by shifting the threshold voltage towards more positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 7 publications
(15 reference statements)
1
14
0
Order By: Relevance
“…where s is the total polarization charge density of conventional HEMT, P PZ (AlGaN) denotes piezoelectric polarization in AlGaN, x is the degree of relaxation, b and l are the fitting parameters. Equations (5), (9), and (10) are brought into Eq. (8), we can obtain the following equation by conversing: where V TH-NC is the threshold voltage of NC-HEMT, V TH-C is the threshold voltage of conventional HEMT.…”
mentioning
confidence: 99%
“…where s is the total polarization charge density of conventional HEMT, P PZ (AlGaN) denotes piezoelectric polarization in AlGaN, x is the degree of relaxation, b and l are the fitting parameters. Equations (5), (9), and (10) are brought into Eq. (8), we can obtain the following equation by conversing: where V TH-NC is the threshold voltage of NC-HEMT, V TH-C is the threshold voltage of conventional HEMT.…”
mentioning
confidence: 99%
“…4 shows the impact of both the Al 45 Ga 55 N top barrier layer thickness and the plasma etching conditions on the threshold voltage of the device. Even though the high power etch facilitates enhancement mode operation by implantation of negatively charged fluorine ions that deplete the channel and shift the V T 1.5 V more positive, it has been shown that these ions are not stable under thermal stress causing a shift of the V T back to more negative voltages (7). Moreover, they induce shallow traps that give rise to DC-to-RF dispersion phenomena (7 -9).…”
Section: Methodsmentioning
confidence: 98%
“…The high power etch causes F -implantation and a resulting VT shift but also dispersion(6)(7)(8). The dashed lines are a guide to the eye.…”
mentioning
confidence: 99%
“…8). The SiN underneath the gate was fully removed down to the AlN barrier layer by using a low-power SF 6 plasma etching optimized in order to avoid damage under the gate [9]. Ni/Au gate metals were deposited using another e-beam lithography step.…”
Section: Rf Power Measurementsmentioning
confidence: 99%